High Boron Silicon Nanotubes Combined with Tai Chi Exercise Rehabilitation Therapy in the Treatment of Knee Arthritis Patients - Guang Ma (Journal of Chemistry)
Tai Chi exercise is gentle, convenient, and easy to learn. It is more economical than traditional medical treatments, and it is regarded as the first choice for rehabilitation therapy by patients with knee arthritis. This article aims to study Tai Chi exercise rehabilitation therapy combined with high boron silicon nanotubes to treat knee arthritis patients. This article mainly introduces the treatment of knee arthritis patients with Tai Chi, which is reflected in the improvement of patients’ walking ability and stability, and explores a three-dimensional motion model to provide better help for patients with knee joints. The article uses data mining methods to collect data on the gene expression of human knee joints and analyzes the causes of knee arthritis caused by its internal structure. The experimental results of this paper show that, under Taijiquan exercise rehabilitation treatment, the time needed by knee arthritis patients to get up and run is reduced by 14%, the standing time of one leg is significantly improved, the fall rate is reduced by 13%, and the body’s static balance ability is improved.